Static and Dynamic Modelling of 1D Heterogeneous Molten Salt Reactors - Andersson, Erik (My University, 2021)
Molten salt reactors represent one of the so called Generation IV concepts. In this design the fuel is dissolved in a molten salt, which also acts as a coolant. The moving fuel introduces a new physical phenomenon not present in reactor designs with stationary fuel. Delayed neutrons, emitted through the decay of certain fission fragment nuclei, called precursors, will in this case be emitted down-stream from where the original fission event occurred. Since the precursor nuclei have mean lives comparable to the temporal scale of the velocity, this will affect the neutron flux in the reactor. There is also the possibility of precursors reentering the core since the molten salt is circulating in the system. This thesis describes the process of developing a novel numerical simulation tool, using the diffusion approximation for neutron flux, for the calculation of the neutron flux and precursor concentration of a one dimensional heterogeneous reactor core. The tool solves the diffusion equations with two energy groups and one group of precursors in the stationary case and for a monochromatic perturbation in the frequency domain, respectively. The eigenvalue problem arising in the stationary case with no external sources is solved using the power iteration method with a Wielandt’s shift technique and the inversion of matrices is done using an LUPQ factorization. For the purpose of testing the implementation, a scaled down solver for one energy group and one group of precursors was developed in the same way as the full solver. When tested, the full solver reproduces the results of a previously developed similar solver for the case of zero fuel velocity and the scaled down version reproduces the results of a previously developed one-group solver as well as the analytical solution to the special case of infinite fuel velocity. A condition on the mesh resolution was found that greatly impacted the dynamic solution for the precursor concentration as its spatial distribution exhibits an oscillatory behaviour.
Keywords: Molten Salt Reactors; two-group neutron diffusion theory; neutron noise; numerical reactor modelling